If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4/3(12x+27)=-57-9x
We move all terms to the left:
-4/3(12x+27)-(-57-9x)=0
Domain of the equation: 3(12x+27)!=0We add all the numbers together, and all the variables
x∈R
-4/3(12x+27)-(-9x-57)=0
We get rid of parentheses
-4/3(12x+27)+9x+57=0
We multiply all the terms by the denominator
9x*3(12x+27)+57*3(12x+27)-4=0
Wy multiply elements
27x^2(1+171x(1-4=0
| 7−2j=1 | | 7u+21=10u | | x=20(90-x) | | x-7=13=20 | | 7x+11/4=-6 | | m+4=-12=16 | | 14x+4-x=-7 | | (7x)-5=11 | | n+16=19=3 | | 5÷2x+1÷4x=9÷4+x | | 7n+1=6 | | x=2x=3 | | 3+p=8= | | 7+z=12.5 | | -7-p=p-7+6 | | 9x2-x-8=0 | | (0.10)(0.5)+0.35g=0.15(g=0.5) | | 2x+8=10x-17 | | 15+b=23= | | 5x+7=7x-2x | | m+4=-12= | | 2(4x+4)=8x-4 | | n+16=19= | | t-12=5.96 | | 16=m-5.3 | | n=16=19 | | -5+5(n-7)=-40+ | | 4x2+7x-1=0 | | n2-n-6=0 | | 180=d×20 | | -87=3(3r+8) | | -12=-(2/3)y |